Pengembangan Website ‘BALASAN’ Sebagai Upaya Peningkatan Minat Belajar Bahasa Isyarat Indonesia - Ramadhan, Fija; Fatiha, Luthfia Jayyida Ainaya; Krisanti, Haeranisa Bella; Rozan, Daffa; Z, Caezario Rafie Anggara (Indonesian Journal Publisher, 2023)
This website development uses fun and interactive methods. This website collaborates with GERKATIN which provides Bisindo classes which discuss understanding the world of the Deaf, how to communicate with the Deaf, and learning the basics of Indonesian Sign Language to build inclusive communication relationships. In this web development, there are 3 Bisindo service options that can be chosen according to your needs. One of the services is the Bisindo class, where we can take direct (face to face) classes accompanied by experienced Deaf teachers. To be able to take this class you can choose a level, namely level 1 & 2. The class schedule starts when the class quota has been met. Each class is held 10 times according to the schedule determined by GERKATIN.